(3NdGUI GdCKQ aj CYjGf GdbQf GdMGOj YTQs - (3eMeO Cejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s
(3ChdgG (B:s
(3Gddge Sgd jGcQje jGef CMUi HdWag GdNdGFb YOOkG , hLYdge HeTjFJg WQGFb bOOkG s
(3BNQgG (B:s
(3hhUd HYOgG Edi bSWfWjfjI aJhai SfI KdGK hSHYjf QMeg Gddg Je s
(3GfXQ HQbe (B1037 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B78s
Keywords: (3GdJGQjNs